HUBUNGAN DAYA LEDAK OTOT TUNGKAI DENGAN KETEPATAN SMASH PADA BULUTANGKIS MAHASISWA IKOR FIKKM DI UNIMA - Natanael Paoki (Jurnal Praba : Jurnal Rumpun Kesehatan Umum, 2024)
The purpose of this study is to determine whether there is a relationship between leg muscle explosiveness and smash accuracy in badminton among IKOR FIKKM UNIMA students. The research method used is descriptive with a correlation technique. The sample for this study consists of 15 students from the IKOR program. The instrument used to measure leg muscle explosiveness is the vertical jump test, while the accuracy of the smash is assessed using a racket, shuttlecock, net, court, and recording tools. The results of the normality test show a value of 0.200, and the linearity test yields a value of 0.780. In the hypothesis test, since the calculated t value is greater than or equal to the table t value, the null hypothesis is rejected. This indicates that there is a significant relationship between leg muscle explosiveness and smash accuracy among IKOR FIKKM UNIMA students. The correlation coefficient between variable X and Y is 0.710, indicating a very significant relationship, as confirmed by the SPSS analysis.